Spleen Tyrosine Kinase Modulates Fibrous Airway Obliteration and Associated Lymphoid Neogenesis After Transplantation. Issue 1 (26th August 2015) - Matsuda, Y.; Wang, X.; Oishi, H.; Guan, Z.; Saito, M.; Liu, M.; Keshavjee, S.; Chow, C.‐W.
Abstract: Chronic lung allograft dysfunction, the major cause of death following lung transplantation, usually manifests as irreversible airflow obstruction associated with obliterative bronchiolitis (OB), a lesion characterized by chronic inflammation, lymphoid neogenesis, fibroproliferation and small airway obliteration. Spleen tyrosine kinase (Syk), a tyrosine kinase that regulates B cell function and innate immunity, has been implicated in the pathogenesis of chronic inflammation and tissue repair. This study evaluated the role of Syk in development of OB, using an intrapulmonary tracheal transplant model of OB with the conditional Syk‐knockout Syk flox/flox //rosa26‐CreER T2 mice and a Syk‐selective inhibitor, GSK2230413. BALB/c trachea allografts were transplanted into Syk‐knockout (Syk del/del ) mice or wild‐type C57BL/6 recipients treated with GSK2230413. At day 28, histological analysis revealed that in the Syk del/del and GSK2230413‐treated C57BL/6 recipients, the graft lumen remained open compared with allografts transplanted into Syk‐expressing (Syk flox/flox ) and placebo control–treated C57BL/6 recipients. Immunofluorescence showed lymphoid neogenesis with distinct B and T cell zones in control mice. In contrast, lymphoid neogenesis was absent and few B or T cells were found in Syk del/del and GSK2230413‐treated mice. These observations suggest that inhibition of Syk may be a potential therapeutic strategy for the management of OB following lung transplantation. Abstract : Inhibition of spleen tyrosine kinase attenuates fibrous airway obliteration following allograft transplant in a mouse intrapulmonary transplant model of obliterative bronchiolitis.